A novel ECEL1 mutation expands the phenotype of distal arthrogryposis multiplex congenita type 5D to include pretibial vertical skin creases. Issue 6 (16th April 2018) - Stattin, Eva‐Lena; Johansson, Josefin; Gudmundsson, Sanna; Ameur, Adam; Lundberg, Staffan; Bondeson, Marie‐Louise; Wilbe, Maria
Abstract : Arthrogryposis multiplex congenita (AMC) is a heterogeneous disorder characterized by multiple joint contractures often in association with other congenital abnormalities. Pretibial linear vertical creases are a rare finding associated with arthrogryposis, and the etiology of the specific condition is unknown. We aimed to genetically and clinically characterize a boy from a consanguineous family, presenting with AMC and pretibial vertical linear creases on the shins. Whole exome sequencing and variant analysis revealed homozygous novel missense variants of ECEL1 (c.1163T > C, p.Leu388Pro, NM_004826) and MUSK (c.2572C > T, p.Arg858Cys, NM_005592). Both variants are predicted to have deleterious effects on the protein function, with amino acid positions highly conserved among species. The variants segregated in the family, with healthy mother, father, and sister being heterozygous carriers and the index patient being homozygous for both mutations. We report on a unique patient with a novel ECEL1 homozygous mutation, expanding the phenotypic spectrum of Distal AMC Type 5D to include vertical linear skin creases. The homozygous mutation in MUSK is of unknown clinical significance. MUSK mutations have previously shown to cause congenital myasthenic syndrome, a neuromuscular disorder with defects in the neuromuscular junction.